Enhancing Sustainability through Efficient Public Spending: Polish Procurement Perspectives (London Journal of Research In Management & Business, 2024)
Sustainability is a leading criterion in sustainable financing decisions, both for financial markets and private actors as well as for public finance. State and local government actors play a key role in implementing and supporting the concept of sustainable finance, but also recognise the special role of non-financial risks (so-called ESG risks - Environmental, Social, Governance), within which environmental, social and governance risks are distinguished.The integration of sustainability and inequality into the public procurement system has brought with it the need for changes in the hierarchy of values affecting the public spending process. One of the demonstrated goals of using sustainable public procurement is to increase the efficiency of public spending. In order to demonstrate and research efficiency gains in the indicated area, it becomes necessary to analyse the role of axiology in the public procurement law system while recognising risks and threats.In 2015, the United Nations (UN) adopted the 2030 Agenda for Sustainable Development. This created a new pathway to improve the lives of countries and societies. The Agenda includes a set of goals that include, among others, eradicating poverty, reducing inequality, improving health and well-being, protecting the planet and ensuring human well-being . All the goals contained in the 2013 Agenda have been grouped into 17 Sustainable Development Goals (SDGs), with the overall goal of creating a better world not only for present but also for future generations .The public procurement procedure has evolved from a typical economic tool to a complex tool that embodies and implements several dimensions of sustainable development, being now a "multi-purpose instrument" . Changes in the sustainability paradigm, the impact of non-financial factors, changes in the perception of the role of finance in financing sustainable development, the need to preserve the financial stability of the public sector, the need to integrate the public financial system with the safety net and, above all, changes in the perception of the environment and the human position in it imply changes in the public finance and procurement paradigm.The analysis underpinning the conclusions is based on the use of quantitative research methodology. In order to collect information and data, the research method of document analysis and analysis of literature was used, which includes in particular reports, regulations of European law, including EU law, and Polish law. The analysis of the quantitative data, in particular the legal analysis, was carried out in order to draw final conclusions and determine the results of the research.
Keywords: Institutional Evaluation. Strategic Anticipation. Higher Education; Civilisations; performance; nepotism; sociometry; culture.